(untitled) (Research, Society and Development, 2026)
In Brazil, cervical cancer incidence and mortality persist at high levels, disproportionately affecting most vulnerable women. This article aims to present and discuss factors that facilitate or hinder the implementation of HPV-based screening, which is important for achieving cervical cancer global elimination targets by 2030. A SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis assessed internal and external factors affecting the nationwide adoption of HPV-based cervical cancer screening. The analysis was informed by official national documents, international guidelines, and peer-reviewed published literature, complemented by insights from researchers, health managers, and civil society actors. The SWOT analysis identified strong enabling factors—including a unified public health system, existing laboratory capacity, and availability of World Health Organization (WHO)-recommended HPV tests—alongside major weaknesses, such as low screening coverage, lack of an organized call–recall system, and regional inequities. Opportunities include global support for cervical cancer elimination, expansion of molecular diagnostics, and the potential of self-collection to reach underserved populations. Threats include supply chain vulnerabilities, long-term financial sustainability, and uncertainties in follow-up pathways for women with HPV-detected. The analysis highlights strategic priorities for strengthening the implementation of HPV-based screening in Brazil, with actionable recommendations to increase coverage, improve diagnostic quality, and enhance follow-up and treatment. These findings can guide planning and support efforts to meet the Global cervical cancer elimination targets.